Lipopolysaccharide preconditioning augments the antibacterial activity of renal macrophages and ameliorates acute kidney injury caused by bacteremia in mice - Keiko Tanoue; Manabu Kinoshita; Bradley M Kearney; Seigo Ito; Hiroyasu Goto; Aoi Yamashiro; Tsugumi Fukunaga; Hiroki Sato; Kazuma Mori; Koji Kuwata; Hidehito Matsubara; Azusa Kato; et al. (Innate Immunity)
Introduction Repeated injections of low-dose lipopolysaccharide (LPS preconditioning) augment the antibacterial activity of liver macrophages. In this study, a mouse model of acute kidney injury (AKI) induced by Staphylococcus aureus (S. aureus) bacteremia was used to investigate the effects of LPS preconditioning on renal macrophages. Methods Eight-week-old C57BL/6J mice were preconditioned with either low-dose LPS (5 μg/kg) or the vehicle for three consecutive days. Kidney immune cells were isolated, and the antibacterial activity of renal macrophages was assessed by pHrodo TM -labeled S. aureus in vitro . Twenty-four hours after the last LPS injection, the mice were intravenously challenged with S. aureus (2 × 10 7  CFU) and their renal function was evaluated to identify the changes. Results Mouse renal macrophages exhibited a weak antibacterial activity against S. aureus compared with the liver and spleen macrophages. LPS preconditioning elevated the count of F4/80 low CD11b high bone marrow-derived macrophages (BMDM) and augmented their antibacterial activities in the mouse kidney. It also enhanced the antibacterial activity of F4/80 high CD11b low tissue-resident macrophages (TRM) without altering their abundance. LPS preconditioning lowered the bacterial propagation in the kidney in the challenged mice and ameliorated sepsis-associated AKI compared with the control. LPS preconditioning upregulated the CD80/CD206 expression (M1/M2) ratio in BMDMs in the kidney before bacterial challenge and reduced their M1/M2 ratio following S. aureus challenge compared with the control. Conclusion LPS preconditioning enhanced the antibacterial activity of the renal macrophages against S. aureus and suppressed the excessive activation of M1 macrophages following S. aureus challenge, resulting in the amelioration of AKI caused by S. aureus bacteremia.